OPTIMASI PENDISTRIBUSIAN BERAS DENGAN PENERAPAN METODE IMPROVED ZERO POINT METHOD PADA PERUM BULOG KANTOR CABANG MEDAN - Muhammad Alfi Syahri Harahap; Cipta, Hendra; Widyasari, Rina (Universitas Cokroaminoto Palopo, 2024)
This study discusses the Implementation of the Improved Zero Point Method in optimizing the distribution of rice at Perum Bulog Medan Branch Office with the goal to be achieved, namely, optimizing or minimizing the cost of distributing rice. In this study, problem solving was solved using the North West Corner Method as the initial solution, and the Improved Zero Point Method as the optimal solution. The results of this study obtained an initial solution, namely, Rp. 11,619,850, then we calculate using the optimal solution we get a reduction in distribution costs of Rp. 8,089,900.